Sustainable Strategy, Risk Management, and Financial Performance of Tourism Operators - Tarjo, Tarjo; Anggono, Alexander; Said, Jamaliah; Halim, Abdul; Sakti, Eklamsia (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2024)
The primary purpose of writing this paper is to empirically demonstrate the role of risk management in mediating the relationship between sustainable strategies and the financial performance of tourism operators comprising hotels, homestays, restaurants, and cafes. Researchers distributed a set of questionnaires to tourism operators in Indonesia and obtained two hundred and fifty respondents. Data was analyzed using Structural Equation Modeling - Partial Least Square (SEM PLS). The statistical tool employed is WarpPLS version 7.0. The first finding of the research is that sustainable strategies have a significant positive impact on the sustainable financial performance of tourism operators. Second, a sustainable approach has a significant positive effect on risk management. Third, risk management has a significant positive impact on the sustainable financial performance of tourism operators. The main discovery of this research is that risk management successfully serves as a mediator in the relationship between sustainable strategies and the financial performance of tourism operators.